2010
DOI: 10.1002/path.2752
|View full text |Cite
|
Sign up to set email alerts
|

Primary effusion lymphoma: genomic profiling revealed amplification of SELPLG and CORO1C encoding for proteins important for cell migration

Abstract: Primary effusion lymphoma (PEL) is associated with Kaposi sarcoma herpesvirus (KSHV) but its pathogenesis is poorly understood. Many KSHV-associated products can deregulate cellular pathways commonly targeted in cancer. However, KSHV infection alone is insufficient for malignant transformation. PEL also lacks the chromosomal translocations seen in other lymphoma subtypes. We investigated 28 PELs and ten PEL cell lines by 1 Mb resolution array comparative genomic hybridization (CGH) and found frequent gains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…The use of cell lines allowed us to study the functional consequences of our analysis, which would not have been possible using only archival specimens. We and others previously reported karyotyping and comparative genome hybridization (CGH) profiles for some PEL (5,(14)(15)(16)(17)(18)(19). Our prior data were array-based and included a survey of known SNVs, which was used as a quality control for this study.…”
Section: Resultsmentioning
confidence: 99%
“…The use of cell lines allowed us to study the functional consequences of our analysis, which would not have been possible using only archival specimens. We and others previously reported karyotyping and comparative genome hybridization (CGH) profiles for some PEL (5,(14)(15)(16)(17)(18)(19). Our prior data were array-based and included a survey of known SNVs, which was used as a quality control for this study.…”
Section: Resultsmentioning
confidence: 99%
“…9 In particular, Coronin3 (Coronin1C) has been associated with metastasis in several cancer types. [10][11][12] In a previous study, we revealed that Coronin3 overexpression promotes GC metastasis both in vitro and in vivo. 13 Metastasis-associated gene analysis indicated that MMP-9 and cathepsin K might play certain roles in the downstream pathways regulated by Coronin3.…”
Section: Introductionmentioning
confidence: 97%
“…Gene expression profile studies in primary effusion/body cavity lymphoma have demonstrated a unique profile relative to other aggressive lymphomas; these results tend to substantiate the distinct clinicopathologic distinction of primary effusion/body cavity lymphomas from other lymphomas (Ueda, et al, 2010). Other studies have demonstrated a number of complex cytogenetic abnormalities as well as a reduction in tumour-suppressor gene expression in primary effusion/body cavity lymphoma (Luan, et al, 2010;O'Hara, et al, 2009); these features may further contribute to the aggressiveness of this lesion. Most published cases appear to be treated with CHOP or derivations thereof.…”
Section: Primary Effusion/body Cavity Lymphomamentioning
confidence: 76%